2022
DOI: 10.3389/fped.2022.888370
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Incidence and Characteristics of Newly Diagnosed Type 1 Diabetes in Chinese Children and Adolescents: A Nationwide Registry Study of 34 Medical Centers

Abstract: ObjectiveTo investigate the clinical incidence and characteristics of type 1 diabetes mellitus (T1DM) of children and adolescents at the time of initial diagnosis in China.MethodsData on all pediatric patients with newly diagnosed T1DM were retrospectively collected from 34 medical centers in 25 major cities in China from January 2015 to January 2020. Patients were classified into three age groups: <5 years, 5 to <10 years, and ≥10 years of age. The same patient population was also categorized in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 55 publications
2
6
0
Order By: Relevance
“…We found that the mean annual incidence of T1DM in children and adolescents in Hubei Province in 2017-2022 was 4.25/100,000, and that this rate gradually increased over the study period. This nding is consistent with previous studies conducted in China [15], which indicates that our data re ect the incidence of T1DM in the general population. However, in both 2020 and 2021, the clinical incidence of T1DM in China was markedly elevated, while the clinical incidence was decreased in 2022.…”
Section: Discussionsupporting
confidence: 94%
See 3 more Smart Citations
“…We found that the mean annual incidence of T1DM in children and adolescents in Hubei Province in 2017-2022 was 4.25/100,000, and that this rate gradually increased over the study period. This nding is consistent with previous studies conducted in China [15], which indicates that our data re ect the incidence of T1DM in the general population. However, in both 2020 and 2021, the clinical incidence of T1DM in China was markedly elevated, while the clinical incidence was decreased in 2022.…”
Section: Discussionsupporting
confidence: 94%
“…However, the frequency of DKA was not higher in patients with idiopathic T1DM than in patients with immune-mediated T1DM, contrary to the hypothesis that SARS-CoV-2 infection leads to a signi cant increase in newly diagnosed autoimmune-negative T1DM [11]. In this study, we also found no increase in the frequency of DKA in the cohort from the COVID-19 pandemic, consistent with the incidence rate of DKA at the onset of T1DM in China [15]. During the COVID-19 pandemic, the Chinese Society of Pediatric Endocrinology and Metabolism developed recommendations regarding the identi cation and treatment of children with critical diabetes, including an e cient and effective treatment plan [24].…”
Section: Discussionsupporting
confidence: 65%
See 2 more Smart Citations
“…4 However, it is important to note that the knowledge acquired from studies based on these registries cannot be directly applied to the Chinese population due to differences in the incidence of T1D, the associations of genetic background, the frequency of islet-related autoantibodies, and the distribution of clinical subtypes between East Asian and Caucasian populations. [5][6][7][8][9][10][11][12][13][14][15][16][17] Several regional studies have been conducted within China, including the Guangdong Provincial Translational Medicine of Type 1 Diabetes, 7 a single-centre retrospective hospital study in Henan, 8 and the 3C study in Beijing and Shantou. 9 These studies have reported the demographic and informatics features, clinical characteristics at onset, complications, and comorbidities of Chinese T1D patients.…”
Section: Introductionmentioning
confidence: 99%